El Excentrico, 1976-11-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, CA; Garcia Printing, 2024)
November 5, 1976 [5 de noviembre de 1976]. Ano 27, No 14. Cover has a photo of Alicia La Paloma del Norte in formal attire.